Eksegesis Penghukuman Allah Bagi Ciptaan - Chia, Philip Suciadi (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
Abstract: There are some similarities and differences between the punishments that the Serpent and Adam received. Either in the reason why it was punished, or the form of punishment received. The common reason for their punishment is that they have similar active actions, but the difference is that the serpent has done (14a) while Adam has listened (17a). The form of punishment received by the serpent was "you are cursed" to receive a direct curse, and what Adam received was "Cursed land". Regarding food, the punishment for snakes is to eat dust, while the punishment for humans is how to get food. Against the ground, the Serpent was humbled from among all that lived in the field, while towards man, the plants that grew in the field were the food of man.Keywords: genesis; judgment; creationAbstrak:Ada beberapa persamaanÂ  dan perbedaan dari hukuman yang diterima olehÂ  Ular dan Adam. Baik dalam alasan mengapa dihukum, atau bentuk penghukuman yang diterima. Kesaamaan alasan penghukuman mereka adalah karena memiliki tindakan aktif yang serupa, namun perbedaannya ular telah melakukan (14a) sedangkan Adam telah mendengarkan (17a). Bentuk penghukuman yang di terima oleh ular adalah â€œengkau dikutukâ€ menerima kutukan langsung, dan yang diterima oleh AdamÂ  adalah â€œTanah dikutukâ€. Perihal makanan, yang menjadi hukuman ular adalah memakan debu sedangkan hukuman terhadap manusia adalah cara mendapatkan makan. Terhadap tanah, ular direndahkan dari antara seluruh yang hidup di ladang, sedangkan terhadap manusia, tanaman-tanaman yang tumbuh di ladang yang menjadi makanan dari manusia.Kata Kunci: kejadian; penghukuman; ciptaan